### Nuprl Lemma : weak-antecedent-surjection-conditional2

`∀es:EO`
`  ∀[P1,Q1,P2,Q2:E ─→ ℙ].`
`    ∀dcd_P1:e:E ─→ Dec(P1 e). ∀f:{e:E| P1 e}  ─→ {e:E| Q1 e} . ∀g:{e:E| P2 e}  ─→ {e:E| Q2 e} .`
`      (∀e:E. Dec(Q1 e)) `` (∀e:E. Dec(Q2 e)) `` Q1 ←←= f== P1 `` Q2 ←←= g== P2 `` Q1 ∨ Q2 ←←= [P1? f : g]== P1 ∨ P2 `
`      supposing ∀e:E. ((P1 e) `` (¬(P2 e)))`

Proof

Definitions occuring in Statement :  weak-antecedent-surjection: `Q ←←= f== P` conditional: `[P? f : g]` es-E: `E` event_ordering: `EO` predicate_or: `P1 ∨ P2` decidable: `Dec(P)` uimplies: `b supposing a` uall: `∀[x:A]. B[x]` prop: `ℙ` all: `∀x:A. B[x]` not: `¬A` implies: `P `` Q` set: `{x:A| B[x]} ` apply: `f a` function: `x:A ─→ B[x]`
Lemmas :  weak-antecedent-surjection-conditional
\mforall{}es:EO
\mforall{}[P1,Q1,P2,Q2:E  {}\mrightarrow{}  \mBbbP{}].
\mforall{}dcd\$_{P1}\$:e:E  {}\mrightarrow{}  Dec(P1  e).  \mforall{}f:\{e:E|  P1  e\}    {}\mrightarrow{}  \{e:E|  Q1  e\}  .  \mforall{}g:\{e:E|  P2  e\000C\}    {}\mrightarrow{}  \{e:E|  Q2  e\}  .
(\mforall{}e:E.  Dec(Q1  e))
{}\mRightarrow{}  (\mforall{}e:E.  Dec(Q2  e))
{}\mRightarrow{}  Q1  \mleftarrow{}\mleftarrow{}=  f==  P1
{}\mRightarrow{}  Q2  \mleftarrow{}\mleftarrow{}=  g==  P2
{}\mRightarrow{}  Q1  \mvee{}  Q2  \mleftarrow{}\mleftarrow{}=  [P1?  f  :  g]==  P1  \mvee{}  P2
supposing  \mforall{}e:E.  ((P1  e)  {}\mRightarrow{}  (\mneg{}(P2  e)))

Date html generated: 2015_07_17-AM-09_02_49
Last ObjectModification: 2015_01_27-PM-00_53_48

Home Index